PERTUMBUHAN KALUS DAUN MELON (Cucumis melo) VARIETAS MAI 119 DENGAN PEMBERIAN BAP (BENZYL AMINO PURINE) DAN 2,4-D (2,4 DICHLOROPHENOXYACETIC ACID) - Toharah, Nining Intan; Jekti, Dwi Soelistya Dyah; Zulkifli, Lalu (Postgraduate, University of Mataram, 2015)
This study aims to determine the concentration of growth regulators BAP and 2,4-D which have the highest effect in stimulating the formation of callus melon plants (Cucumis melo) Mai 119 variety. Completely randomized design (CRD) was used in this research. Media used on callus induction was MS medium with addition of several concentration of BAP (0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L) and 2,4-D (0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L) either alone or in a combination of both. Parameters measured were the time appearing of callus, callus diameter, callus texture, and callus color. Anova followed by Tukey's test was used to the analyse of time appearing of callus. Data of callus diameter was analyzed using Kruskal Wallis test followed by Mann-Whitney test. In the analysis of parameter related to the callus texture and callus color, descriptive test were used. The results showed that there were differences in the effect of growth regulators on the callus formation. The fastest callus induction and the largest diameter of callus were obtained on media with concentration of 2 mg/L BAP and 3 mg/L BAP.Keywords: BAP (benzyl amino purine), 2,4-D (2,4-dichlorophenoxyacetic acid), callus induction, melon (Cucumis melo) varieties Mai 119